ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DALAM PEMECAHAN MASALAH MATEMATIKA KELAS XI MA DARUL ULUM - Ummi Khairiyah; Darsih Idayani; Yesi Puspitasari (STKIP PGRI SITUBONDO, 2020)
Research to describe communication skills mathematical students in solving mathematics problems class XI MA Darul Ulum 2019/2020 school year. This research is descriptive qualitative research. The subjects in this study were students of class XI MA Darul Ulum as many as 3 students with different levels of communication ability. Data collection in this study uses 4 methods namely; observation, interviews, problem solving tests, and documentation are then analyzed on each data collection method. The results showed that all subjects understand the problem well and have planning and solving problems well, but at low-communication subjects are not good at doing problem solving planning. It shows the wrong results while the subject of high and fair communication ability are showing correct results. It can be concluded that the level of communication skills different mathematical solutions have different problems.